Preparative Isolation and Purification of Phlorizin from Apple Tree Bark by High-Speed Counter-Current Chromatography - Xu, K.; Deng, R.; Lu, H.T. (Asian Journal of Chemistry, 2011)
Phlorizin, abundantly existed in apple tree bark, has been found to be highly active in transporter and antioxidant activity. Using high-speed counter-current chromatography, the separation and purification of phlorizin from the crude phlorizin extract of apple tree bark was achieved. It was performed at a preparative scale in one-step separation with a two-phase solvent system composed of chloroform-methanol-n-butanol-water (5:4:0.5:3, v/v). The lower phase was used as the mobile phase in the head-to-tail elution mode. By injecting 606 mg of the crude phlorizin extract, 89.5 mg of phlorizin with the purity of 99.0 % were yielded. Its chemical structure was confirmed by UV, FTIR, ESI-MS, 1H and 13C NMR analysis. Furthermore, the optimum extracting conditions of phlorizin from apple tree bark were also investigated by orthogonal test L16 (43).